Methylation modification of non-histone proteins in breast cancer: An emerging targeted therapeutic strategy - Mingyao Huang; Zirong Jiang; Yadan Xu; Chaoshen Wu; Wei Ding; Xuli Meng; Da Qian (Elsevier, 2024)
Breast cancer is a major public health concern worldwide, being the most commonly diagnosed cancer among women and a leading cause of cancer-related deaths. Recent studies have highlighted the significance of non-histone methylation in breast cancer, which modulates the activity, interaction, localization, and stability of target proteins. This regulation affects critical processes such as oncogenesis, tumor growth, proliferation, invasion, migration, and immune responses. This review delves into the enzymes responsible for non-histone methylation, such as protein arginine methyltransferases (PRMTs), lysine methyltransferases (KMTs), and demethylases, and explores their roles in breast cancer. By elucidating the molecular mechanisms and functional consequences of non-histone methylation, this review aims to provide insights into novel therapeutic strategies targeting these pathways. The therapeutic potential of targeting non-histone methylation to overcome drug resistance and enhance treatment efficacy in breast cancer is also discussed, highlighting promising avenues for future research and clinical applications.